ChemInform Abstract: From Protected‐Hydroxy Acylsilanes to Functionalized Silyl Enol Ethers and Applications in Mukaiyama Aldol Reactions. Issue 25 (June 2016) - Ruiz, Johal; Karre, Nagaraju; Roisnel, Thierry; Chandrasekhar, Srivari; Gree, Rene
Abstract: The reaction of protected β‐hydroxy acylsilanes (I) and (XII) with sulfones provides (E)‐silyl enol ethers, whereas the reaction with Grignard reagent (V) give the (Z)‐isomers (VI) as sole products.